INCREASING PROFITABILITY OF MEAT PROCESSING UNITS BY ADDING VALUE FOR MEAT TRIMMINGS - Olga DRĂGHICI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the meat industry, after the cutting, deboning and trimming phases, meat trimmings result from which minced meat is usually made. From an economic point of view, the superior utilization of meat trimmings is of interest. A method analyzed in this paper consists of the injection of trimmings in the meat muscle. The results obtained indicated a lower weight gain if the meat is injected with brine emulsion (between 8.37% and 9.84%) compared to samples injected only with brine (41.20% for pork ribeye and 45.7% for beef ribeye). However, protein content is inversely correlated with weight gain (r2=-0.88). The main disadvantage of the method lies in the fact that it decreases the preservability of the meat injected with meat emulsion compared to the control samples.